Inclined MHD Effects in Tapered Asymmetric Porous Channel with Peristalsis: Applications in Biomedicine - Anum Tanveer; Sharak Jarral (Science, Engineering and Technology, 2023)
This paper emphasized an inclined magnetohydrodynamics (MHD) effects in tapered asymmetric porous channel with peristalsis in the presence of slip boundary conditions. Here we considered the two-dimensional channel with a porous medium. The fundamental assumptions of long wavelength and low Reynolds number are applied in the relevant nonlinear equations for momentum, heat, and mass transfer as part of mathematical modeling. The equations subjected to slip boundary conditions have been solved numerically by the Mathematica software. Various essential physical characteristics of velocity, temperature, concentration, and heat transfer rate are captured graphically in the end. The velocity profile is found parabolic for various involved parameters. It is observed that the embedded parameters behave in the exact opposite manner when compared with temperature and concentration distributions. The sinusoidal behavior of the heat transfer rate is also displayed. The unique aspect of this effort is specifically to relate the Joule heating, Darcy resistance, and inclined magnetic field effects in peristaltic flow for a non-Newtonian Jeffrey fluid in an asymmetric tapered channel under the influence of slip boundary conditions. Such preferences have a wide range of applications in engineering, biology, and industry. The outcomes of the presented work are also proficient in the medical field for the treatment of cancer using MHD. The MHD also aids in controlling blood pressure during systolic and diastolic pressure conditions by regulating the blood flow stream.